PENGARUH KEPERCAYAAN, WORD OF MOUTH, KUALITAS PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN - Riska Putri Septia Ardhana; Ginanjar Rahmawan (JURNAL ILMIAH EDUNOMIKA, 2022)
Currently, skincare is a very important mandatory requirement for women because basically every woman always wants to look beautiful. Due to the COVID-19 pandemic, many activities are carried out at home. This makes not a few people who experience skin problems that look dull and unhealthy. These problems can be overcome by using skincare. The purpose of this research is to find out trust, word of mouth, product quality and lifestyle affect the purchasing decisions. The number of respondents used in this research is 97 with the criteria that consumers have used Scarlett Whitening. Data collection is by means of questionnaires, using multiple linear regression analysis tools. This research shows that trust, word of mouth, product quality and lifestyle have a significant effect on purchasing decisions. Keyword: Trust, Word Of Mouth, Product Quality, Lifestyle, Purchasing Decisions